Wpływ zmian powierzchni zieleni miejskiej w Poznaniu na parametr CN metody SCS i współczynnik spływu powierzchniowego - Jawgiel, Kamil; Łukaszewicz, Jan (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
Land use changes are important in water circulation. Already at the stage of water supply to basin precipitation it’s modified into effective precipitation and then filters into the substrate or runs off the surface of the area. Identifying the significance of these changes is key in setting the limits for urbanization in terms of water management and flood protection. The most commonly used method for calculating the precipitation effect that causes outflow is the SCS method. The underlying assumption of this method is the dependence of effective precipitation on the type of land cover, soil and soil moisture. This article presents the application of this method in the context of the study of surface runoff in an urbanized area, where changes in land use during the last century have influenced the runoff.
Keywords: surface runoff; SCS CN; land use changes; Poznan; runoff coefficient